Revisiting the automation tax debate in light of Covid-19 and resulting structural unemployment - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2020)
As lockdowns ease around the globe and businesses reopen, the threat of jobs being automated by machines and workers being displaced as a result has significantly increased. Businesses must keep the number of workers on site to a minimum to comply with safe distancing measures. Under these constraints while social distancing remains the norm, automation might be the way forward for companies that still want to continue production while minimising human contact. The threat of a workforce being replaced by robots and automation, a threat that has already alarmed the labour movement, is heightened with Covid-19. There will be considerable layoffs.